Management decisions for engineers - Parkin, James (Thomas Telford, 1996)
Decision making is at the heart of managing. This book is a guide, designed for engineering managers, to the theory and practice of how good decisions are made and why poor decisions occur.
Keywords: Engineering -- Management.; Civil engineering -- Decision making.; elektronické knihy; electronic books